KYIV’S LOGO (CHESTNUT) AND ITS PLACE IN THE DESIGN OF THE CAPITAL’S PRODUCTS - Shapoval, Anatoliy; Maznichenko, Oksana; Osadcha, Alla (Theory and practice of design, 2023)
The purpose of this publication is to systematize and generalize information about the chestnut as the logo of Kyiv and its place in product design in the capital of Ukraine. Methodology. The publication uses the following research methods: comparative (when comparing different logos), typological and descriptive methods of analyzing the role of logos in advertising, generalization (for summing up the intermediate and final results of the research, formulating conclusions), a comprehensive approach (allowed to subjugate the elements of the content and form of the proposed article aims and objectives of the research). The results. The article establishes the main historical milestones of the evolution of the chestnut as an emblem of Kyiv. Scientific novelty. Reasoned approaches to the development of a marketing strategy for the use of the chestnut as the logo of Kyiv. Practical significance. The conclusions obtained in the article can be used during the preparation of educational materials on the history of Kyiv advertising. Conclusions. It was revealed that the chestnut became one of the symbols of Kyiv during the tsarist period, and the logo of Kyiv during Soviet times. Chestnut leaf is used in design in the capital of Ukraine – from subway tokens to souvenirs and clothes. Proposed stages of purposeful image formation of Kyiv using the chestnut logo: preparatory; definition of the strategy and concept of corporate style of Kyiv; selection of the main idea of corporate style from all options and its visualization; logo development; detailed elaboration of corporate style elements; development of the beech brand; patent protection of corporate style. The «Kyiv chestnut» logo can be used on business cards, folders, postcards, envelopes, booklets, forms, calendars, on souvenir products, as well as on food packaging («Kyiv cake», etc.). The structures of local government and the city community in general have already realized the benefits that Kyiv is able to receive with appropriate use and a scientifically defined approach in the implementation of its identity system.